Implementation of business intelligence tools using open source approach - Gameiro, Carlos Alberto Monteiro (2013)
Discovering business intelligence is the modern organization’s way of gaining competitive advantage in their market, supported by Decisions Support Systems or Business Intelligence Systems. The first step in any decision support system is to create the repository of data for the system to collect and display any information requested. This repository is the source of all business intelligence and implementing it requires the right software tools, essential for the data warehouse. Therefore, when choosing the software tool, the project size, budget constraints and risks should be kept in mind. Overall the right choice depends on the organization’s needs and ambitions. The essential work to be done here is to demonstrate that open source software can be an accurate and reliable tool to implement data warehouse projects. The two ETL solutions used were: • Pentaho Kettle Data Integration Community Editions (Open Source Software) • SQL Server 2005 Integrations Services (SSIS) Enterprise Edition (Proprietary Software) The proprietary, commercial software in question (as well as others) is widely used. However, an open source solution has key features recognized by organizations worldwide and this work will show the different functionalities and benefits of this open source approach.